1982
DOI: 10.1152/jappl.1982.53.6.1620
|View full text |Cite
|
Sign up to set email alerts
|

Fate of exogenous glucose during exercise of different intensities in humans

Abstract: The extent to which an oral load of glucose is absorbed from the gut and oxidized during prolonged exercise is a matter of controversy. Four healthy volunteers, 18-28 yr, were submitted on 4 different days to a 105-min treadmill exercise at 22, 39, 51, and 64% of their individual VO2max. After 15 min adaptation to exercise, they received orally 100 g naturally labeled [13C]glucose. Oxidation of the exogenous glucose was followed by 13CO2 measurements in the expired air; total carbohydrate and lipid oxidation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 0 publications
8
48
2
Order By: Relevance
“…This could be related to the greater dependance of muscle on glucose for energy release during intensive training. 34 Another interesting ®nding in this study is the decrease in fat oxidation between the 7th and 14th week of training. This was observed under standardised conditions (controlled light-activity programme and composition of food intake, neutral daily energy balance) and occurred despite a 3% increase in FFM.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This could be related to the greater dependance of muscle on glucose for energy release during intensive training. 34 Another interesting ®nding in this study is the decrease in fat oxidation between the 7th and 14th week of training. This was observed under standardised conditions (controlled light-activity programme and composition of food intake, neutral daily energy balance) and occurred despite a 3% increase in FFM.…”
Section: Discussionmentioning
confidence: 74%
“…This situation is known to stimulate carbohydrate metabolism at the expense of FFA oxidation. 34 Moreover, it is well known that endurance training improves insulin sensitivity in young adults as well as in elderly people 35,36 and improved insulin action has been associated with a higher glucose uptake at the muscle level. 35 Moreover, under hyperinsulinaemic hyperglycaemic conditions, insulin andaor glucose have been shown to inhibit fat oxidation by controlling the rate of long chain FFA entrance into the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the effect of exercise intensity on ingested CHO oxidation Pirnay et al (1982), examined four different exercise intensities At higher (> 70% V02max) exercise intensities, the oxidation of ingested CHO are not known. In theory, high exercise intensities reduce ingested CHO oxidation by slowing splanchnic blood flow and intestinal absorption (Barclay and Turnberg 1987;Maughan et al 1990;Williams et al 1964).…”
Section: Effect Of Exercise Intensitymentioning
confidence: 99%
“…7 It was only after the late 1970's and early 1980's that 13c and 14c labelling techniques were used to calculate rates of ingested CHO oxidation during exercise (Lefebvre et al 1975;Lefebvre et al 1979;Pirnay et al 1977aPirnay et al , 1977bPirnay et al , 1982Jandrain et al 1984Jandrain et al , 1989Krzentowski et al 1984;Massicotte et al 1986Massicotte et al , 1989Massicotte et al , 1990Pallikarakis et al 1986;Peronnet et al 1990;Hawley et al 1992a;Moodley et al 1992). Such studies were, on the whole performed on cyclists, possibly because it is easier to take blood from a cyclist on a stationary ergometer that from a runner on a treadmill.…”
Section: Introduction and Historical Overviewmentioning
confidence: 99%
“…Using isotopic methodologies, combined with indirect calorimetry, this latter study also showed that exogenous glucose oxidation peaked and reached a plateau at a rate of ϳ195 mg/min at the lower ingestion rate of 400 mg/min. Interestingly, this oxidation rate was one-third less than what is found during exercise eliciting a similar metabolic rate (28). Glucose ingestion also modified the utilization of endogenous glycogen reserves.…”
mentioning
confidence: 67%